Pergeseran Standar Feminisme Dalam Pemilu AS: Studi Terhadap Postfeminisme di Kalangan Muda [The Shifting Feminist Standard in U.S. Elections: Studies on Postfeminism in Youth] - Tri Indah Oktavianti; Muhammad Nur Hasan (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2017)
Feminism firmly stands in the front line when it comes to the confrontation against injustice and oppression. Yet, feminism has become too exclusive for the subject of women and privileged for sub-groups like whites and middle-class, who stand as a whole category. By then, feminism is stuck in a time warp as it is unable to diminish the oppression of binary gender and its exclusive category. Under the framework of post-structuralist feminism theory, post-feminism is defined as a positive development of feminism that offers more comprehensive thinking. This research aims to identify the ideas of post-feminism and analyze how the shifting values of feminism towards post-feminism occur. Through interpretive methods, the researcher identified that post-feminism was about the deconstruction of the subject 'women' and inter-sectionalism. The millennial paradigm shifts in the United States allowed the creation of preferences that was diverse and unlimited to a specific gender perspective. Thus, the political preferences of feminists were not only limited to the assumption of women that should choose a female president. Therefore, supporters of the millennial wave phenomena of Bernie Sanders in the primary caucus of Democratic Party of US elections in 2016 became one of the reflections of the millennial post-feminism ideas.